Bedside echocardiography is useful in assessing children with fluid and inotrope resistant septic shock - Ranjit, Suchitra (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: To report changes in the cardiovascular management of fluid and inotropic resistant septic shock in children based on echocardiography. DESIGN: Retrospective case series. SETTING: Tertiary care Pediatric Intensive Care Unit (PICU), Chennai. PATIENTS: Twenty-two patients with unresolved septic shock after 60 ml/kg fluid plus inotropic agents in the first hour. INTERVENTIONS: Bedside echocardiography (echo) within 6 h of admission to the PICU. RESULTS: Over a 28-month period, of 37 patients with septic shock, 22 children remained in shock despite 60 ml/kg fluid and dopamine and/or dobutamine infusions as per guidelines. On clinical exam, 12 patients had warm shock and ten had cold shock, however, six exhibited an unusual pattern of cold shock with wide pulse pressures on invasive arterial monitoring. The most common echocardiographic finding was uncorrected hypovolemia in 12/22 patient while ten patients had impaired left ± right ventricular function. Echocardiography permitted an appreciation of the underlying disordered pathophysiology and a rationale for adjustment of treatment. Shock resolved in 17 (77%) and 16 patients (73%) survived to discharge. CONCLUSIONS: Bedside echo provided crucial information that was not apparent on clinical assessment and affords a simple noninvasive tool to determine the cause of low cardiac output in patients who remain in shock despite 60 ml/kg fluid and inotropic support. Most patients in our series had vasodilatory shock with wide pulse pressures and most common finding on echo was uncorrected hypovolemia. The echo findings allowed adjustment of therapy which was not possible based on clinical examination alone.